Posttraumatic cranial nerve injury - Purav Patel; S Kalyanaraman; J Reginald; P Natarajan; K Ganapathy; KR Suresh Bapu; A Vincent Thamburaj; P Chendilnathan; M Balamurugan (The Indian Journal of Neurotrauma, 2005)
Injury to the cranial nerves is a common accompaniment of head trauma. Incidence of cranial nerve injury in head injury varies in various published literature. Indian literature on post-traumatic cranial nerve injuries as whole is scanty. Aims of this study are to document the incidence of cranial nerve injuries in head injuries, to correlate incidence with radiological findings, to assess recovery time with respect to signs and symptoms at initial presentation and to stress the importance of clinical examination in head injured patients. We studied 794 consecutive cases of head injured patients from May 2002 to November 2004. One hundred patients were found to have cranial nerve injuries and were included in this study. Clinical examination of cranial nerves was done meticulously on a daily basis. Patients were followed up at monthly interval for a minimum of six months.